POTENSI MINYAK JAHE MERAH DAN MINYAK JERUK MANIS SEBAGAI BAHAN AKTIF ALAMI DALAM PEMBUATAN HANDSANITIZER - Jhelsia Sisilia Tandikura; Sophia Grace Sipahelut; Gelora Helena Augustyn (Universitas Pakuan, 2022)
The COVID-19 pandemic that has hit the world requires everyone to maintain hand hygiene as a way to avoid this virus. Hand sanitizer is an instant option for cleaning hands. The use of essential oils in hand sanitizers is considered safer than alcohol. This study aims to study the antiseptic activity, physical and organoleptic characteristics of hand sanitizers in combination with red ginger oil and sweet orange oil. This study was designed using a completely randomized design (CRD) with one factor, namely a combination of red ginger oil and sweet orange oil, with three treatment levels: 75% : 25%, 50% : 50%, dan 25% : 75%. Parameters analyzed included antisepticby Replika method, dispersibility, pH, density, homogeneity and organoleptic tests (texture, aroma, and color). The results showed that hand sanitizer with a combination treatment of 25% red ginger oil and 75% sweet orange oil had a stronger antiseptic effectiveness compared to other treatments. 6.2 cm which shows the consistency of the hand sanitizer that is comfortable when used, the hand sanitizer gel is homogeneous, without any coarse grains and is still organoleptically acceptable for texture, aroma and color.